2007 Paco peca - Grupo Teatro La Cochera (2017)
Autoría: Paco Giménez, Marcelo Massa | Actúan: Paco Giménez | Dirección: Marcelo Massa | Consultado el 27 de julio de 2016 | http://www.alternativateatral.com/obra8300-paco-peca